General Overview of Intracranial Meningiomas: 11 Years of Experience in an Oncological Reference Center - Corrêa, Antônio Carlos de Souza; Couto, Maíra Piani; Monteiro, Andrew Moraes; Macedo, Bernardo Felipe Santana de; Brito, José Reginaldo Nascimento; Lemos, Rafael Silva; Andrade, Gabrielly Leite; Fernandes, Manuela Rodrigues Neiva (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
To perform the clinical and therapeutic follow-up of patients with meningioma and to evaluate the risk and protective factors for the outcomes obtained during the treatment.We conducted a retrospective cohort study using clinical, radiological, and histopathological data contained in the records of patients with meningiomas; we also performed retrospective monitoring for 5 years, evaluating the initial symptoms and clinical evolution, demographic data, risk factors, location, laterality and dimensions, treatment, complete radiological resection, death, additional deficits, and changes in the performance score.We followed up a sample of 86 patients with a mean age of 47 years and a predominance of female subjects. The most frequent histological types were the meningothelial, followed by the fibrous, the transitional subtype, and the mixed and psamomatous subtypes. Grade-II and -III injuries represented 8.13% and 3.12% of the total respectively. The initial clinical conditions presented nonspecific signs in 79% of the individuals and focal neurological signs in 12%, the most common being appendicular deficit, unilateral amaurosis, and cranial nerve syndrome. Regarding treatment distribution, all patients studied underwent surgical resection (Simpson 1: 15%; Simpson 2: 12%; Simpson 3: 35%; and Simpson 4: 36%), with a good correlation of the total radiological resection for the first 3 degrees.Thus, the need for early diagnosis and therapy is emphasized to achieve a better outcome, and we recommend the performance of prospective studies that evaluate other variables to clarify the risk factors for mortality and recurrence.
Keywords: meningioma; follow-up; survival analysis; neurosurgery